Using on-line journals to stimulate reflective thinking - Fairholm, Eilean; Dougiamas, Martin; Dreher, Heinz (Centre of Educational Advancement, Curtin University, 2000)
Information Systems or Electronic Commerce students can take HTX212 in their bachelor's program, or HTX512 in their graduate diploma and master's programs. These are combined into one face to face unit, supported by the use of WebCT, and consolidated by a three person team project, where students attempt to incorporate the features of client-side and server-side Web programming and database management which they have been taught. Other aims of the unit are to consolidate core skills learnt in other units; particularly project management, and to develop the use of reflective thinking for process improvement. This paper describes a partially successful attempt to stimulate private communication from students with their lecturers through the use of structured questions in a WebCT journal. Having discussed the techniques used, and examined the student responses to the questions posed, the paper concludes by suggesting improvements for the future. The weekly journal requirement from each student to audit their and their team's performance allowed each individual to share concerns with their lecturers, analyse where processes were not working, suggest and monitor the effect of improvements. The quality of student response improved throughout the semester, with some deep discussion of issues, although many students struggled with the concept initially. Discussions were promoted on the bulletin board.